مسلم معاشروں میں معاشی عدل وانصاف کا قیام: سیرتِ طیبہ کی روشنی میں ایک مطالعہ: Establishing Economic Justice and equity in Muslim Societies: A Study in the light of the Sīrah of the Prophet (Al-Qamar, 2025)
This research explores the establishment of economic justice and equity in Muslim societies in the light of the Seerah of the Prophet Muhammad ﷺ. Islam, being a natural and comprehensive religion, offers complete guidance for human physical and spiritual needs, including economic matters. The study highlights that Islamic economic thought is rooted in core principles such as Tawheed (monotheism), Khilafah (human stewardship), accountability, and social welfare, which collectively emphasize equitable distribution of wealth and the eradication of exploitation, poverty, and injustice. Qur’anic commands, Prophetic practices, and the economic policies of the early Islamic state—including prohibition of usury, establishment of Zakat, promotion of fair trade, encouragement of lawful earning, and mutual economic support—form the foundation of Islamic economic justice. The Seerah demonstrates a balanced system where wealth is considered a trust from Allah and must circulate broadly rather than concentrate in a few hands. The economic model of Madinah—marked by market regulation, social solidarity, protection of workers’ rights, financial transparency, and institutional support mechanisms such as Zakat and Waqf—serves as a timeless framework for equitable development. The study concludes that adopting the Prophetic model of socio-economic justice can enable contemporary Muslim societies to overcome economic inequality, corruption, and poverty, thereby ensuring social harmony and sustainable development based on divine guidance ethical values, and human dignity.
Keywords: Pophetic Seerah; Islamic Economics; Economic Justice; Wealth Distribution; Zakat System; Social Welfare; Anti-Usury (Riba); Khilafah; Economic Equity; Ethical Trade; Islamic Welfare State